Liquefaction Characteristics of Sand With Polypropylene Fiber at Low Confining Stress - Tripathi, Sudhir K.; Kolay, Prabir K.; Puri, Vijay K.; Kumar, Sanjeev (Frontiers in Built Environment, 2020)
The present study evaluates the liquefaction characteristics of Ottawa sand with polypropylene fiber using cyclic triaxial test. A series of stress-controlled cyclic triaxial tests were performed at 34.47 kPa (5 psi) effective confining pressure. Specimens of clean Ottawa sand, and sand containing 0.05, 0.075, 0.1, and 0.3% polypropylene fiber by dry weight of sand were tested at 0.2, 0.25, 0.3, and 0.4 Cyclic Stress Ratio (CSR). Results show that a significant improvement in liquefaction resistance when the polypropylene fiber content exceeded beyond 0.075% at 34.47 kPa effective confining stress.